1992
DOI: 10.1111/j.1439-0418.1992.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Life table parameters of the two phytoseiid predators Amblyseius scutalis (Athias‐Henriot) and A. swirskii A.‐H. (Acari, Phytoseiidae) in Egypt

Abstract: Life history of the two phytoseiid species Amblyseius scutalis (= Euseius scutalis (A.‐H.) and A. swirskii A.‐H. was studied at constant conditions 26 ± 1 °C and 70% ± 3 RH to compare their life tables and effeciency as biological control agents. Developmental stages of mite female of both A. scutalis and A. swirskii fed on nymphs of Tetranychus urticae Koch durated 7.81 and 5.50 days, respectively. Preoviposition, oviposition and postoviposition periods lasted 2.86 and 1.87; 12.86 and 22.33; 11.40 and 5.12 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 6 publications
10
29
0
Order By: Relevance
“…However, these results are in agreement with that reported by Abou-Awad et al, (1999) El-Laithy and Fouly (1992) when reared the predator on the two spotted spider mite Tetranychus urticae Koch and that of Metwally et al, (1984) who reared the predator on the citrus brown mite Eutetranychus orientalis Klien. It is worth noting that feeding the predator on each of the four prey did not result in a significant effect on the rate of development of the different stages (Tables 1 & 2).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, these results are in agreement with that reported by Abou-Awad et al, (1999) El-Laithy and Fouly (1992) when reared the predator on the two spotted spider mite Tetranychus urticae Koch and that of Metwally et al, (1984) who reared the predator on the citrus brown mite Eutetranychus orientalis Klien. It is worth noting that feeding the predator on each of the four prey did not result in a significant effect on the rate of development of the different stages (Tables 1 & 2).…”
Section: Resultssupporting
confidence: 81%
“…Life Comparing the life table parameters of T. swirskii with those of other workers carried out under almost similar conditions showed that the net reproduction rate (Ro) and the mean generation time (T) were 13, 17 on T. urticae (El-Laithy and Fouly, 1992) and 16, 17 on E. orientalis (Aly, 1994), respectively; but on the fig bud mite A. ficus, the predator population could multiply 21 times in a generation time of 20 days (Abou-Awad et al, 1999). Here again, eriophyid mites proved to be more suitable prey for phytoseiid mites than tetranychids.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic rate of natural population increase is similar for both species (Cloutier et al, 1995;Lee & Gillespie, 2011). The life cycle of A. swirskii feeding on spider mite nymphs at 26 o C, 70% RH was 5.5±0.5 days (El-Laithy & Fouly, 1992). Amblyseius swirskii generally live for 27.87±2.4 days and lay approx.…”
Section: Acari (Mites)mentioning
confidence: 81%
“…Amblyseius swirskii generally live for 27.87±2.4 days and lay approx. 27.8±3.8 eggs during their oviposition period (El-Laithy & Fouly, 1992). A population of A. swirskii increases most quickly when fed its preferred prey of thrips or whiteflies; although, as a polyphagous generalist predator, A. swirskii will feed on other prey if preferred prey are not available (Gerson & Weintraub, 2007;Messelink et al, 2005).…”
Section: Acari (Mites)mentioning
confidence: 99%
“…It is a recent addition to the beneficial assortment, developed and marketed by the Dutch producer of beneficial, Koppert B.V. (van Houten et al, 2005). It is capable to prey on spider mites (Swirski et al, 1967;El-Laithy and Fouly, 1992;Momen and El-Saway, 1993;van Houten et al, 2007).…”
Section: Introductionmentioning
confidence: 99%